2009
DOI: 10.1179/175889709x446543
|View full text |Cite
|
Sign up to set email alerts
|

Coalescence of bubbles in liquid

Abstract: Coalescence of bubbles is important for the destabilisation of gas-liquid dispersions. The theories of coalescence used at present are reviewed. The film drainage theory and the stochastic theory of coalescence have been discussed with their merits and drawbacks. The influence of van der Waals, electrostatic double layer, steric and solvation forces on the coalescence process has been discussed. The importance of adsorption of surfactant molecules at the air/water interface in presence and in absence of salt o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 55 publications
0
16
0
Order By: Relevance
“…It was shown that the coalescence time has stochastic distribution for all studied surfactants. Good agreement was established between the coalescence time and the foamability of the surfactant solutions studied [16][17], which shows that the lifetime of individual bubbles can be used to predict the stability of real foams. However, in most of these studies the bubbles with relatively large size were used, around 2.5 mm.…”
Section: Introductionmentioning
confidence: 65%
See 2 more Smart Citations
“…It was shown that the coalescence time has stochastic distribution for all studied surfactants. Good agreement was established between the coalescence time and the foamability of the surfactant solutions studied [16][17], which shows that the lifetime of individual bubbles can be used to predict the stability of real foams. However, in most of these studies the bubbles with relatively large size were used, around 2.5 mm.…”
Section: Introductionmentioning
confidence: 65%
“…Due to its practical importance, the coalescence stability of foams was extensively studied in the literature for many years [11][12][13][14][15][16][17][18][19][20]. In the course of these studies it was found that there is a critical capillary pressure, above which the foams become unstable [11][12], as well as the existence of threshold air volume fraction, above which the rate of bubble coalescence dramatically increases [13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 Generation of foam during consumer usage can be either desired or undesired depending on the application. For example, in a front-loader fabric washing machine or machine dish-wash, foam is undesirable.…”
Section: Introductionmentioning
confidence: 99%
“…2a). Coalescence of bubbles, which is a very complex process, 37,38 is generally needed in the production of scaffolds. To enable the fabrication of highly interconnective porous network, the gas forming method has been modified by combining with particulate leaching (such as NaCl).…”
Section: Physically Pressed Gas Foaming and Its Combination With Partmentioning
confidence: 99%